Progam Caring Untuk Merentensi Pelanggan Telkom Flexi - Tri Diah Cahyowati; Mutiara Leinsove Sara (Universitas Mercu Buana, 2008)
GIStomers ore the most important CSFiect of a bust', less. Company^ success in prouiding customer sati^faction is highly dependent on the @6nit:I to sati1^ customers and ultimately to retain its customers. PT. Talkomunikosifndonesia is a company engaged in thefteld of telecommunications services. Related in thenIce of competition CD^,;!4. -based telecommunication business which currently tight, PT. Talkom South Jakarta to implement a strategyCttstomerRetentionMorketing (CRM)to keep customers Flea'. Flexi'customersin maintaining the Talkor, IFle, cz'implement Marketing costomerRetentionintheformqfaretentionprogrom calledCaring Program24. fntheCaringProgromis24TelkontFle:c, ' make customer retention t^ff'orts, cmong others, streamline and improue the uoriot, s channels ofir!formotion Gridcommttnication with customers, to establish interaction and improue relations with customers.